Analisis Rantai Nilai Pemasaran Kopi (Value Chain) di Kabupaten Aceh Tengah - Sofyan Samsudin; Herlinawati Herlinawati (Jurnal Agrisep, 2016)
Aceh Tengah is a district of coffee production center in Aceh Province. The purpose of this study was to determine 1. The structure, behavioral and performance of the market. 2. To analyze the Value Chain of Arabica coffee marketing in Aceh Tengah. Population in this study were 82 respondents of farmers, 8 people merchant trader, big traders 4 people, 2 exporter and 5 businessmen who worked as a processor, roasted coffee and coffee powder. The sampling technique used is snowball sampling technique. This study uses analysis structure conduct performance (SCP), which examines the marketing of coffee from the farm to the final consumer, the added value in terms of the processing of fresh coffee into a coffee roaster and coffee powder. Results of the analysis showed that the arabica coffee marketing in the research area has four marketing channels, the market tends to be oligopsony structure market. Concentration of market showed results of 1.4, the most powerful concentration, and Minimum Efficiency Scale (MES) at 11.6%, which means that there are barriers to market entry. The highest profit margin contained in the wet green coffee processing offenders become coffee roasting reaching IDR 28.700,- per Kg whereas the Share Farmer highest at 91% are the perpetrators of large merchants by performing the processing grain coffee into a green wet coffee just to exfoliate the outer skin of coffee, then sell it to the exporter. The value chain marketing value chain in the processing of arabica coffee contains of primary and support activities. Coffee processing can be seen in the coffee roasting process which has added value ratio up to 19% per Kg. While the ratio of value added in the processing of coffee powder is 7.74% per Kg. The feedback that is needed is to increase the role of government and institutions in arabica coffee marketing to increase revenues parties involved in such activity.